Leveraging artificial intelligence as a learning tool in higher education - Mncedisi Christian Maphalala; Oluwatoyin Ayodele Ajani (Interdisciplinary Journal of Education Research)
The integration of Artificial Intelligence (AI) technologies in education has gained significant attention, particularly in the context of higher education, in recent years. Despite concerns about academic integrity, academics recognise the opportunity for AI to foster critical thinking and prepare students for real-world scenarios. However, its integration into courses requires careful consideration of course objectives and ethical implications. This study explores the utilisation of AI in higher education settings, focusing on its role as a learning tool. The study systematically reviewed 87 empirical studies from databases between 2014 and 2024 to investigate the benefits, challenges, and implications of incorporating AI into higher education. Additionally, it examines the potential impact of AI on teaching methodologies, student outcomes, and the overall learning experience. The findings of this study underscore the significant influence of AI integration in higher education on teaching methodologies. This integration promotes personalised and adaptive instruction, enhancing student engagement, performance, satisfaction, and overall learning experiences. However, the adoption of AI in higher education raises significant ethical concerns that demand careful consideration. These concerns include data privacy, algorithmic bias, intellectual property rights, and academic integrity. Academics' perspectives on AI adoption vary based on technological proficiency, pedagogical beliefs, and institutional support. Successful AI integration necessitates alignment with pedagogical theories such as constructivism, connectivism, and self-directed learning, ensuring a robust technical infrastructure and addressing ethical considerations to maximise benefits while minimising risks.